2015
DOI: 10.1177/1535370215595468
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 28 is overexpressed in human glioblastomas and contributes to glioma tumorigenicity by regulating MYC expression

Abstract: The transcription factor MYC, which is dysregulated in the majority of gliomas, is difficult to target directly. Deubiquitinase ubiquitin-specific protease 28 (USP28) stabilizes oncogenic factors, including MYC. However, the contribution of USP28 in tumorigenesis, particularly in glioma, is unknown. Here, we determined the expression of USP28 and assessed its clinical significance in human glioma. We found that USP28 is overexpressed in human glioma but not in normal brain tissue. The level of USP28 protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…USP13 was found preferentially expressed in GSCs while SCF FBXL14 was predominantly expressed in non-stem glioma cells, enabling preferential stabilization of c-Myc in GSCs. USP28 was previously shown to stabilize c-Myc in HeLa and U2OS cells by antagonizing SCF FBW7a -mediated degradation and a more recent study has now reported its overexpression in GBM (269,313). It has also been demonstrated that high expression of TRIP13, which stabilized c-Myc by inhibiting FBW7 transcription, correlates with poor patient survival (203).…”
Section: Stem Cell Maintenancementioning
confidence: 98%
“…USP13 was found preferentially expressed in GSCs while SCF FBXL14 was predominantly expressed in non-stem glioma cells, enabling preferential stabilization of c-Myc in GSCs. USP28 was previously shown to stabilize c-Myc in HeLa and U2OS cells by antagonizing SCF FBW7a -mediated degradation and a more recent study has now reported its overexpression in GBM (269,313). It has also been demonstrated that high expression of TRIP13, which stabilized c-Myc by inhibiting FBW7 transcription, correlates with poor patient survival (203).…”
Section: Stem Cell Maintenancementioning
confidence: 98%
“…The mechanism remains unclear for the positive regulation of USP28 on c-MYC in human gliomas. 58 Bladder cancer It remains unclear for the role of USP28 in bladder cancer.…”
Section: Targeting Usp28 In Intestinal Cancermentioning
confidence: 99%
“…Importantly, USP28 promoted MYC expression, which was required for USP28-induced cell growth in human glioma. Therefore, USP28 could be a new target of therapy for human malignant gliomas 58 .…”
Section: Targeting Usp28 In Intestinal Cancermentioning
confidence: 99%
“…In addition to its role in the p53 pathway, USP28 was also shown to stabilize the oncogene c-MYC after DNA damage. The same authors and others found high expression levels of this DUB in colon, lung, glioma, bladder, and breast carcinomas ( Popov et al, 2007a , b ; Diefenbacher et al, 2014 , 2015 ; Guo et al, 2014 ; Wang Z. et al, 2016 ). USP36 and USP37 also control the stability of c-Myc and thereby affect c-Myc oncogene driven cellular proliferation ( Zhang et al, 2006 ; Pan et al, 2015 ; Sun et al, 2015 ).…”
Section: Regulation Of P53 C-myc and Other Oncogenes By Dubsmentioning
confidence: 65%